ANALYSIS OF STUDENTS’ COMMUNICATION ABILITIES AND MATHEMATICS LOGIC THINKING IN GENERATIVE LEARNING WITH SCIENTIFIC APPROACH OF CLASS XI STUDENTS MAJORING IN HEALTH ANALYS AT SMK KESEHATAN MEGA REZKY IN MAKASSAR - A.Wiwik Pratiwi Fujiwijaya (Universitas Negeri Makassar, 2016)
The research is a combination of quantitative-qualitative (mixed method). The design of mixed method used is Concurrent Triangulation Design aims to describe be communication ability and mathematics logic thinking of students in generative learning and to discover the improvement of communication ability and mathematics logic thinking of students in generative learning of class XI students Majoring in Health Analys at SMK Kesehatan Mega Rezky in Makassar. The population of the research were all of the students in class XI at SMK Kesehatan Mega Rezky in Makassar. The sample consisted of one class, namely class XI Majoring in Helath Analys as the experiment class taught by using generative learning model chosen by using random sampling technique. The subjects of the research were three students consisted of one student with high mathematics ability, one student with medium mathematics ability, and one student with low mathematics abilitiy. The data of research consisted of mathematics communication data and mathematics logic thinking ability data. The instruments used in collecting the data were mathematics communication ability test, mathematics logic thinking ability test, learning implementation observation sheet, and interview guidance. The data of mathematics communication ability and mathematics logic thinking were analyzed by using descriptive and inferensial analysis and analyzed qualitatitvely. The results of the research reveal that : (1) the implementation of generative learning model in Circumference nd Area of Two Dimensional Figure material is well implemented, (2) the improvement of students’ communication abilities after being taught by implementing generative learning model with average 0.63 is in medium classification, (3) the improvement of students’ mathematics logic thinking abilities after being taught by implementing generative learning model with average 0.59 is in medium classification, (4) mathematics communication ability in generative learning such as the subject who have high, medium, and low mathematics abilities have ability to state mathematics ideas in writing and drawing it, although the picture/sketch made by the subjects with high and low mathematics ability are still not correct. Then, the subject who have high, medium, and low mathematics abilities have ability to interpret and evaluate mathematics ideas in writing although the subject who have high, medium, and low mathematics ability can only write most of the reason/proof which are correct. Moreover, the subjects who have high, medium, and low mathematics abilities also have in using terms, mathematics notations, and its structures to model mathematics situation or problem, although the subjects who have medium and low mathematics abilities can only write most of terms, notations, and mathematics structure correctly, (5) mathematics logic thinking ability in generative learning such as the subjects who have high, medium, and low mathematics ability have ability in thinking orderly, namely the subject with high, medium and low mathematics abilities write the acknoledged information and are questioned in question items completely and correctly, and write correct formulation to solve the problems. Then, the subjects who have high, medium, and low mathematics abilities have argument ability, namely student can write reason/proof in deciding solving stages which can be used to answer questions, although the subjects with medium and low mathematics abilities write the reason which still is not correct but the subjects can solve the questions correctly. Then, the subject with high, medium, and low mathematics abilities have ability to write formulation of conclusion by using their own languages based on the purpose of the question and answer correctly.